Experiments in finance - A survey of historical trends - Christoph Huber; Michael Kirchler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
Experiments can complement other methods in identifying causal relationships and in measuring behavioral deviations from theoretical predictions. While the experimental method has long been central in many scientific disciplines, it was almost nonexistent in finance until the 1980s. To survey the development of experiments in finance, we compile a comprehensive account of experimental studies published in the Journal of Finance, Journal of Financial Economics, Review of Financial Studies, Review of Finance, Journal of Quantitative and Financial Analysis, and Journal of Banking and Finance-as well as of experimental finance studies published in the Top 5 journals in economics. With this novel dataset, we identify historical trends in experimental finance. Since the first experiments where published in finance journals in the 1980s, and especially in the last 20 years, the share of experimental publications in these journals has increased strongly. We report trends towards descriptive experiments, individual decision experiments, and field experiments.
Keywords: B41; C90; G00; G41; 330; Experimental finance; laboratory experiments; field experiments; survey